2014
DOI: 10.12659/msm.892055
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Transversus Abdominis Plane Block on Cost of Laparoscopic Cholecystectomy Anesthesia

Abstract: BackgroundUse of transversus abdominis plane (TAP) block for postoperative analgesia is continuously increasing. However, few studies have investigated intraoperative effects of TAP block. We aimed to study the effects of TAP block in terms of cost-effectiveness and consumption of inhalation agents.Material/MethodsForty patients undergoing laparoscopic cholecystectomy were enrolled in this study. Patients were randomly divided into 2 groups: Group 1 (n=20) patients received TAP block and Group 2 (n=20) patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 18 publications
0
7
1
Order By: Relevance
“…In many previous studies of the use of a TAP block in patients undergoing laproscopic cholecystectomy, there were no differences in terms of the haemodynamic parameters and the duration of anaesthesia between the study groups; and no complications were observed. 6 , 11 , 13 Similarly, there were no differences between the two groups in the present study in terms of demographic characteristics, duration of anaesthesia, haemodynamic parameters and the patient satisfaction scores.…”
Section: Discussioncontrasting
confidence: 48%
“…In many previous studies of the use of a TAP block in patients undergoing laproscopic cholecystectomy, there were no differences in terms of the haemodynamic parameters and the duration of anaesthesia between the study groups; and no complications were observed. 6 , 11 , 13 Similarly, there were no differences between the two groups in the present study in terms of demographic characteristics, duration of anaesthesia, haemodynamic parameters and the patient satisfaction scores.…”
Section: Discussioncontrasting
confidence: 48%
“…A total of 77 articles were relevant to the search terms, and 15 studies were potentially eligible for inclusion. After reading the full-text articles, 7 studies [ 17 , 18 , 19 , 20 , 21 , 22 , 23 ] covering 355 participants were finally included into this review. The flow diagram for the selection is shown in figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Risk assessment as recommended in the Cochrane Handbook is listed in table 2 . Six included studies clearly reported the methods of randomization [ 17 , 18 , 19 , 20 , 21 , 23 ] and 3 detailed the methods of double blinding [ 17 , 18 , 19 , 20 , 21 , 23 ]. Because of the small number of trials included, funnel plots for publication bias could not be reliably examined.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations